PENGARUH BUDAYA ORGANISASI DAN ROTASI PEKERJAAN TERHADAP MOTIVASI KERJA UNTUK MENINGKATKAN KINERJA PEGAWAI - Yakup, Yakup; Suyanto, Mohamad Afan; Karundeng, Deby Rita; Basole, Susan (Universitas Dharmawangsa, 2024)
This study aims to explore the influence of organizational culture and job rotation on work motivation and employee performance. The research method used is quantitative by involving respondents from several companies. The results of the study show that organizational culture and job rotation have a significant effect on work motivation. In addition, work motivation also has a significant positive effect on employee performance. These findings provide a better understanding of the factors that can increase employee motivation and performance in the context of organizational culture and job rotation. The practical implication of this research is the need for greater attention to organizational culture that encourages employee initiative, participation, and involvement, as well as the importance of implementing job rotations that enable employees to develop their skills and knowledge. This can make a positive contribution to work motivation and employee performance. The academic implication is that this research can become the basis for further research in exploring more about the influence of other factors that may influence employee motivation and performance, as well as in developing more effective human resource management strategies and programs.